2004
DOI: 10.1080/10473289.2004.10470927
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Ion Characteristics During the Big Bend Regional Aerosol and Visibility Observational Study

Abstract: The ionic compositions of particulate matter with aerodynamic diameter Յ2.5 m (PM 2.5 ) and size-resolved aerosol particles were measured in Big Bend National Park, Texas, during the 1999 Big Bend Regional Aerosol and Visibility Observational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Several field experiments were designed and conducted to investigate the chemical composition of PM 2.5 aerosol and the concentrations of trace gases (HNO 3 , NH 3 and SO 2 ) at monitoring locations for the IMPROVE program from the late 1990's through 2010 ( Aerosol composition measured at these sites has previously been reported (Yu et al, 2005b(Yu et al, , 2006Lee et al, 2004Lee et al, , 2008a. In addition, a series of yearlong intensive measurements were made in Rocky Mountain National Park (November 2008-October 2009, daily), Boulder, WY (December 2006-December 2010, 3 and 4-day average), and Brush and Loveland, CO (December 2008-November 2009.…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…Several field experiments were designed and conducted to investigate the chemical composition of PM 2.5 aerosol and the concentrations of trace gases (HNO 3 , NH 3 and SO 2 ) at monitoring locations for the IMPROVE program from the late 1990's through 2010 ( Aerosol composition measured at these sites has previously been reported (Yu et al, 2005b(Yu et al, , 2006Lee et al, 2004Lee et al, , 2008a. In addition, a series of yearlong intensive measurements were made in Rocky Mountain National Park (November 2008-October 2009, daily), Boulder, WY (December 2006-December 2010, 3 and 4-day average), and Brush and Loveland, CO (December 2008-November 2009.…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…At high temperature, most of the ammonium nitrate will dissociate and exist as gaseous nitric acid and ammonia [7] . The observed seasonal change of the ammonium and nitrate in the fine particles are in accordance with the seasonal change of ambient temperature.…”
Section: Concentrations and Compositions Of Ions In Pm 25mentioning
confidence: 99%
“…Gaseous nitric acid (HNO 3 ) can react with sea-salt particles to form coarse mode sodium nitrate. While nitrate formed by reaction of HNO 3 with NH 3 is in fine particles, NH 4 NO 3 is volatile and likely dissociates to gaseous HNO 3 and NH 3 at low relative humidity (RH) and high temperature [7] . It was found that the fine mode NH 4 NO 3 increased greatly in recent years in east Asia due to the increasing emissions of anthropogenic pollutants and the decreasing concentration of coarse particles [8] .…”
Section: Introductionmentioning
confidence: 99%
“…The filters were allowed to equilibrate at 22 o C and 35% RH for 24 hours prior to weighing. After weighing, exposed Teflon filters were extracted in deionized water and analyzed by ion chromatography for determination of particulate sulfate [50]. Before sampling the quartz filters were baked in air at 550°C for at least six hours to remove any residual carbon.…”
Section: Dilution Samplermentioning
confidence: 99%